Pengaruh Layanan Bimbingan Kelompok Menggunakan Konseling Realitas Terhadap Kepercayaan Diri Siswa - Fahmi, Muhammad Yasir; Lubis, Lahmuddin; Rusman, Abdul Azis (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
This study aims to determine the effect of group counseling using reality counseling on increasing student self-confidence at MTs Al-Washliyah Kedaisianam Batubara. This research is quantitative research with quasi-experimental research methods. The design used in this research was before (pretest) measurements were carried out and after (posttest) treatment was carried out. There are two groups, namely the experimental and control groups. The results showed that (1) the average pretest score for the control group was 112.666 and the average posttest score obtained was 113.93. (2). The average pretest score of the experimental group was 107.2. The average posttest score obtained was 120.533 (3). The average score of control group students increased by 1.26. The average score of experimental group students increased by 13.533. The difference in the average increase in the posttest score between the experimental group and the control group was 12.26. So the average score of the experimental group after carrying out group guidance was higher than the average score of the control group. (4). The increase in posttest scores obtained by all students in the experimental group showed that all students in the experimental group experienced an increase in self-confidence after carrying out group guidance. (5) Based on independent sample t test statistical calculations, the value obtained is 3.28. The value of ????ℎi????????????g is 1.70. Then it is obtained > , namely 3.28 > 1.70, the hypothesis which states that there is an effect of group guidance on the self-confidence of Class VIII MTs Al-Washliyah Kedaisianam Batu Bara is accepted. (6) Acceptance of the research hypothesis shows that the implementation of group guidance has an influence on students' self-confidence. Group guidance has an influence in increasing students' self-confidence.